Inspiracje biblijne we wczesnej poezji Symeona z Połocka - Kozak, Barbara (Acta Polono-Ruthenica, 2010)
The culture of Baroque nurtured reflection upon the human predicament and human relal- tions with God. Many literary texts of the period delved into the obscurity of human destiny, death and the Last Judgement, calling for prudency and christian obedience. For those reasons the Bible was the primary inspiration and constituted the canon of intellectual discourse. Biblical texts, particularly the Old Testament writings, were also potent sources of poetical stimuli for Baroque authors. The Gospels in turn were considered sacred, Jesus and Holy Mary untouchable by the vulgarity of poetic creations. Gospel themes appeared in the poetic writngs of the Baroque only to spread and emphasise the importance of christian ethics as illustrated by the birth, martyrdom and death of Jesus. Motifs and threads of the Gospels are also evident in the early works of Symeon of Polock which exemplifies a deeply religious character of his poetry.